TARGETED SURVEILLANCE OF AVIAN INFLUENZA IN WILD BIRDS USING DOMESTIC DUCKS (CAIRINA MOSCHATA) AS SENTINELS - Rondón E., Juan (2013)
A targeted surveillance method was applied for the early detection of the Avian Influenza Virus (AIV) in the wild birds of the Puerto Viejo’s wetlands in Cañete, Lima, Peru. Twelve 16-week-old domestic ducks of the Muscovy variety (Cairina moschata) were used as sentinels. The ducks, with negative serology and virus isolation to AIV and Newcastle disease, were introduced to the surrounding areas of the wetlands for 70 days during the 2006 winter in order to interact with the resident wild birds. A preliminary identification of the wild bird species present during the study period was done and the interaction degree between both bird populations was subjectively determined. Health status of sentinel birds was assessed by regular clinical examinations as well as cloacal swab and blood samplings, both for virus isolation and for the detection of antibodies against the AIV by the agar gel immune-diffusion (AGID) test. Throughout the study no antibodies were detected, neither was the AIV isolated. The negative results obtained in the evaluations that were performed under the conditions of the study and the time it lasted suggest the absence of the IVA and its horizontal transmission in the populations of wild birds of the Puerto Viejo’s wetlands.